Antecedents of Students' Entrepreneurial Intentions in Indonesia: The Moderating Effect of Parental Involvement - Rolando, Benediktus; Mulyono, Herry (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study addresses the issue of higher education graduates in Indonesia favoring employment over entrepreneurship by examining the factors influencing entrepreneurial intentions among students at private universities in the Jabodetabek area, with a focus on the moderating role of parental involvement in the relationship between entrepreneurship education, academic support, and entrepreneurial intentions. Data were collected from 143 respondents through online questionnaires using a Likert scale, with a non-probability purposive sampling technique. The data analysis, conducted using SmartPLS 4 and Structural Equation Modeling (SEM), revealed that entrepreneurship education and academic support have significant direct effects on entrepreneurial intentions. Specifically, the T-statistic for entrepreneurship education was 4.831, exceeding the critical threshold of 1.65, with a P-value of 0.000, indicating a strong and significant positive influence on entrepreneurial intention. Similarly, academic support yielded a T-statistic of 3.253 and a P-value of 0.001, confirming a significant positive impact on entrepreneurial intention. However, parental involvement did not significantly moderate these relationships, as evidenced by a T-statistic of 1.399 (P-value of 0.162) for the moderation of entrepreneurship education and a T-statistic of 1.504 (P-value of 0.109) for the moderation of academic support, both of which fall below the required threshold of 1.65. These results suggest that while entrepreneurship education and academic support are critical in fostering entrepreneurial intentions, parental involvement does not significantly enhance their effects in this context. To promote entrepreneurial intentions among Indonesian students, it is recommended that educational institutions and government bodies implement curriculum improvements and provide additional support, while also encouraging parents to offer meaningful guidance and resources to support their children's entrepreneurial aspirations.